Intraoperative Fascia Tension as an Alternative to Component Separation. A Prospective Observational Study - Niebuhr, Henning; Aufenberg, Thomas; Dag, Halil; Reinpold, Wolfgang; Peiper, Christian; Schardey, Hans Martin; Renter, Marc Alexander; Aly, Mohamed; Eucker, Dietmar; Köckerling, Ferdinand; Eichelter, Jakob (Frontiers in Surgery, 2021)
Incisional hernias represent frequent late complications in abdominal surgery. The incidence rate is about 20% one year after laparotomy. A giant hernia is often preceded by severe peritonitis of various causes. The fasciotens® Abdomen Device is used to stretch the fascia in a measurably controlled manner during surgery to achieve primary tension-free abdominal closure. The aim of this prospective observational study is to clarify the extent to which the traction method can function as an alternative to the component separation (CS) methods.